Clinical and Healthcare Resource Use Outcomes between Dual-plane and Prepectoral Techniques in Implant-based Breast Reconstruction: A Multicenter Retrospective Study. Issue 3 (14th March 2023) - Bruno, James R.; Brown, C. Coleman; Gabriel, Allen; Parikh, Mousam; Anastassopoulos, Kathryn P.; Lee, Kenneth R.; Daniel, Shoshana; Naik, Rupali; Patel, Reema; Patel, Vaishali D.
Abstract : Background: This multicenter, retrospective study compared clinical outcomes and healthcare resource use in patients who underwent dual-plane (DP) or prepectoral (PP) implant-based breast reconstruction (IBR) after mastectomy in the United States. Methods: Medical records were selected for patients at five sites undergoing immediate one-stage direct-to-implant (first hospitalization) or two-stage IBR (first and second hospitalization) using either DP or PP. Inverse probability of treatment weighting was used to adjust for potential confounders. Complications and healthcare resource use were assessed with logistic regression; pain severity was assessed with ordinary least-squares regression. Results: After inverse probability of treatment weighting, data from 255 patients (DP = 130, PP = 125) and 441 breasts (DP = 226, PP = 215) were analyzed. Mean pain severity scores were lower with PP versus DP immediately after IBR for first ( P = 0.0002) and second hospitalizations ( P = 0.0145), and before discharge for first ( P < 0.0001) and second hospitalizations ( P = 0.0002). A greater proportion of PP versus DP patients had a shorter hospital length of stay (≤ 23 hours) for first hospitalization ( P = 0.0052); proportions were similar for second hospitalization ( P = 0.5499). Intravenous narcotics were prescribed less frequently to PP versus DP patients during first (61.1% versus 69.8%, respectively; P = 0.1486) and second (37.5% versus 55.3%, respectively; P = 0.0172) hospitalizations. Complication rates were low in both groups after first hospitalization discharge (DP: 13.6%, PP: 12.5%, P = 0.7225). Conclusion: This retrospective study suggests that the PP technique in IBR may offer benefits related to clinical outcomes and health resource utilization; however, larger studies, including randomized controlled trials, are needed to confirm.